EVALUASI SIFAT FISIK TABLET FLOATING FUROSEMIDE DENGAN MATRIKS CARBOPOL - ASA FALAHI (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2023)
Furosemide is a sulfonamide-derived diuretic drug which is an alternative treatment for heart failure. Furosemide was made into slow-release tablets to improve the criteria for poor furosemide and maximize its absorption in the stomach. The purpose of this study was to determine whether floating furosemide tablets with a concentration of 23% carbopol matrix could meet the requirements for evaluating the physical properties of tablets compared theoretically with the literatur. The research design used was pre-experimental. In this study, the results of the weight uniformity test showed that there were no deviations from column A and column B, tablet hardness test with an average of 5.4 kg, tablet friability test with a % friability value of 0.08%, floating lag time test with an average time of 184 seconds, and the floating duration time test is with an average time of 8 hours. From the research data, it can be concluded that the floating furosemide tablet with a carbopol matrix concentration of 23% fulfills all evaluations of the physical properties of the tablet